Dealing with bullying - Cambridge Educational (New York : Cambridge Educational, 2011)
This video addresses the root causes and potential solutions to bullying dilemmas. Studying the verbal, emotional, and social aspects of bullying and cyberbullying as well as physical harassment and attacks, the program also distinguishes between bullying that is typically male and typically female--revealing the wide range of results that all forms can have, from hurt feelings to academic problems to murder and suicide. Dramatizations and expert commentary highlight specific strategies to combat this disturbing challenge to American education and the well-being of its young people
DVD format
Keywords: Bullying; Bullying in schools; Cyberbullying